English language instructors’ beliefs about the role of L1 in English language development and formal instruction in Croatia: A survey - Erk Mirna (ExELL (Explorations in English Language and Linguistics))
Current understanding of second language acquisition processes is based on the position that second language learners rely and depend on their L1 as well as on all of their language-related experience. This paper presents results of a questionnaire study aimed to explore Croatian EFL instructors’ beliefs about the role of L1 in English language development and formal instruction. Data was further analysed in order to explore variables most likely to impact instructors’ belief systems (participants’ age and academic degree, students’ language level, learning setting). The findings point to a lack of professional consensus with regard to L1 use which is discussed and followed by practical implications.